SPIN-BASED MEMORY: MEMRISTIVE DEVICES AND ITS APPLICATIONS - Singh, Raj Kumar; Mamta, Kumari (European Scientific Journal, ESJ, 2014)
We present, a none exhaustive one, the current state of the progress in memristive devices and their applications in electronic, spintronic and biological neural network domain starting from the proposition by Leon O. Chua, the father of the concept of memristive devices, to the current state of the work in this field. Starting from the general definition, we have surveyed upon various devices exhibiting memristive behavior viz. thermistors (whose internal state depends on the temperature), spintronic device (whose resistance varies according to their spin polarization) and a biological model, including the Hewlett-Packard (HP) memristor (where the change in resistance is realized by the ionic motion of oxygen vacancies activated by current flow), the first realized memristive device in the laboratory. Memristor and memristor based circuits finding application in analog memory and computing, analog devices, temperature sensor, superconducting emulator and mazes problem solver have been reported.